REBRANDING UMKM CATERING MELALUI DESAIN PACKAGING DAN PROMOSI MEDIA SOSIAL - Hidayat, Azamul; Febriana, Poppy; Rochmaniah, Ainur; Bisri, Muhammad Hasan (LPPM Universitas Nusa Mandiri, 2024)
The problem faced in the Mbok Ndut Catering and Bu Sri Catering catering businesses is that there is no label on the packaging and does not have media as a promotion, so it requires rebranding the packaging design in the form of labels and promotion of the business on social media. The purpose of this community service activity is to provide solutions to the problems being faced. The method used is to provide training in the form of tutorials on how to manage Instagram accounts and how to operate the Google Maps application. The results of this community service are to help the two MSME players create a logo design, create an official Instagram account, create a content design for Instagram posts, create a packaging design in the form of labels, add the location of the Catering business address through the Google Maps Application, train or teach the two MSME players, manage Instagram by posting the menu that we provide with interesting content, and how to operate the Google Maps Application. Thus, in the future it can make it easier for the two MSME players to introduce their business to the wider community.